Error Analysis of Land Plot Cadastral Cases in The Republic of Lithuania - Sabaitytė, Krista; Stanionis, Arminas (Jaunųjų mokslininkų darbai, 2018)
The aim of the research is to identify the biggest and most common errors in creating land plot cadastral cases. Land plot cadastral cases for the analysis were taken in random order from the National Land Service under the Ministry of Agriculture of the Republic of Lithuania. The land plot cadastral cases were gathered from the 10 biggest territories of the National Land Service subdivisions. Most common errors and the main legislations that were breached in the land plot cadastral cases were determined.
Keywords: land plot cadastral cases; land plot plan; real estate cadastre; real estate register